Culturally speaking: - Genzel, Rhona B. (Heinle & Heinle, 1994)
Students learn to speak and act comfortably in a new culture by sharing cultural thoughts, notions, and experiences, and comparing these with the behaviors, customs, and everyday situations common to life in North America.